Determinants of financial reporting quality: Local government status as moderator - Yudhanto, Satrio Kusumo; Rahmawati, Evi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research Aims: This study aims to examine the effect of capital expenditure and local government size on financial reporting quality, with local government status as a moderating variable in Indonesian local governments.Design/Methodology/Approach: The study was conducted on municipal and district governments in Indonesia, covering 379 districts and 87 municipalities, with a total sample of 466 local governments. Data collection was carried out through documentation, with data sourced from audited financial reports of local governments by the Supreme Audit Board. Hypotheses were tested using Moderated Regression Analysis (MRA) with the Eviews 12 software.Research Findings: The results of this study indicate that the variables of capital expenditure and local government size have a significant positive effect on the financial reporting quality of local governments in Indonesia. Furthermore, the local government status variable can moderate the effect of capital expenditure on financial reporting quality, but it cannot moderate the effect of local government size on financial reporting quality in Indonesian local governments.Theoretical Contribution/Originality: This study adds local government status as a moderating variable for the relationship between capital expenditure, local government size, and financial reporting quality.